ONLINE MARKETING STIMULI STRATEGY AND IMPULSIVE BUYING TENDENCY - K.A., Pavan; Vidhya, S. (The journal of contemporary issues in business and government, 2021)
Introduction of faster and cheaper internet connection provide Indian customers a new horizon to explore for shopping at their convenience. This study predominantly deals with how online shoppers impulsive buying tendency trigger with that of marketers E-Commerce marketing strategy. Multiple Regression was used to analyze objectives and it was found that marketing stimuli strategy like Web store quality, and Product display are significantly related with the cognitive impulsive buying tendency. In case of Affective impulsive buying tendency only pricing as well as promotion offers were significant.